Hijacking the translation apparatus by RNA viruses - Bushell, Martin (The Rockefeller University Press, 2002)
As invading viruses do not harbor functional ribosomes in their virions, successful amplification of the viral genomes requires that viral mRNAs compete with cellular mRNAs for the host cell translation apparatus. Several RNA viruses have evolved remarkable strategies to recruit the host translation initiation factors required for the first steps in translation initiation by host cell mRNAs. This review describes the ways that three families of RNA viruses effectively usurp limiting translation initiation factors from the host.